2021
DOI: 10.3390/atmos12070891
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Metal Levels in Urban Dust, Their Methods of Determination, and Risk Assessment

Abstract: This review gives insights into the levels of metals in urban dust, their determination methods, and risk assessment. Urban dust harbors a number of pollutants, including heavy metals. There are various methods used for the sampling of urban dust for heavy-metal analysis and source-apportionment purposes, with the predominant one being the use of plastic sampling materials to avoid prior contamination. There are also various methods for the determination of metals, which include: atomic absorption spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…The fine road dust particles more easily diffuse into the atmosphere than sediments from the geological origins. Toxic metals in fine urban dust can pose potentially serious health risks to residents via pathways of ingestion and inhalation (Adamiec and Jarosz-Krzeminska 2019;Kaonga et al 2021). Many studies have reported that urban dust is severely contaminated with toxic metals, and Zn is more polluted than other metals (Skorbilowicz et al 2020;Jeong et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The fine road dust particles more easily diffuse into the atmosphere than sediments from the geological origins. Toxic metals in fine urban dust can pose potentially serious health risks to residents via pathways of ingestion and inhalation (Adamiec and Jarosz-Krzeminska 2019;Kaonga et al 2021). Many studies have reported that urban dust is severely contaminated with toxic metals, and Zn is more polluted than other metals (Skorbilowicz et al 2020;Jeong et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…DPs are important routes for loading HMs into the human body [ 19 ]. The health risks posed by HMs in indoor and outdoor DPs have attracted particular attention [ 20 , 21 , 22 ]. https://journals.sagepub.com/action/doSearch?target=default&ContribAuthorStored=Naimabadi%2C+Abolfazl Previously, Naimabadi et al.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate urban pollution by metals, especially in Mandalay. Previous studies found that Cu, Cd, Zn, As, Hg, and Pb concentrations were high in urban road dust influenced by vehicle sources (brake linings and tires), industrial activities, and coal burning activities and so on (Benhaddya et al, 2016;Kaonga et al, 2021;Wei et al, 2015).…”
Section: Metals Concentration In Road Dustmentioning
confidence: 94%